The Importance of Poly(ADP-Ribose) Polymerase as a Sensor of Unligated Okazaki Fragments during DNA Replication - Hanzlikova, Hana; Kalasova, Ilona; Demin, Annie A; Pennicott, Lewis E; Cihlarova, Zuzana; Caldecott, Keith W (Molecular cell, 2018)
Poly(ADP-ribose) is synthesized by PARP enzymes during the repair of stochastic DNA breaks. Surprisingly, however, we show that most if not all endogenous poly(ADP-ribose) is detected in normal S phase cells at sites of DNA replication. This S phase poly(ADP-ribose) does not result from damaged or misincorporated nucleotides or from DNA replication stress. Rather, perturbation of the DNA replication proteins LIG1 or FEN1 increases S phase poly(ADP-ribose) more than 10-fold, implicating unligated Okazaki fragments as the source of S phase PARP activity. Indeed, S phase PARP activity is ablated by suppressing Okazaki fragment formation with emetine, a DNA replication inhibitor that selectively inhibits lagging strand synthesis. Importantly, PARP activation during DNA replication recruits the single-strand break repair protein XRCC1, and human cells lacking PARP activity and/or XRCC1 are hypersensitive to FEN1 perturbation. Collectively, our data indicate that PARP1 is a sensor of unligated Okazaki fragments during DNA replication and facilitates their repair.
Keywords: DNA vazebné proteiny; oprava DNA; Poly Adenosine Diphosphate Ribose; DNA Damage; Poly(ADP-ribose) Polymerases; buněčné linie; DNA-ligasa ATP; DNA; lidé; poly(ADP-ribosa)polymerasa 1; S Phase; replikace DNA; DNA Repair; Flap Endonucleases; Cell Line; "flap" endonukleasy; Poly (ADP-Ribose) Polymerase-1; poškození DNA; DNA-Binding Proteins; poly(ADP-ribosa)polymerasy; X-ray Repair Cross Complementing Protein 1; S fáze; DNA Replication; protein XRCC1; DNA Ligase ATP; polyadenosindifosfátribosa; Humans